Evidence-based periodontal plastic surgery: an assessment of quality of systematic reviews in the treatment of recession-type defects - Chambrone, Leandro; Faggion Junior, Clóvis Mariano; Pannuti, Claudio Mendes; Chambrone, Luiz A. (Journal of clinical periodontology, 2010)
OBJECTIVE: To assess methods, quality and outcomes of systematic reviews (SRs) conducted to evaluate the effectiveness of root coverage (RC) procedures in the treatment of recession-type defects (RTD). - METHODS: MEDLINE and EMBASE were searched up to and including April 2010 to identify SRs investigating the effectiveness/efficacy of surgical interventions for the treatment of patients with RTD. Searching was conducted independently by two reviewers, and data extraction was based on the methodological criteria applied and on the effects of interventions reported by each SR. The checklist proposed by Glenny and colleagues, the Overview Quality Assessment Questionnaire and the "Assessment of Multiple systematic Reviews", instrument were used to assess the quality of SRs. Additionally, the methodological criteria applied by included reviews were compared with those proposed by the Cochrane Collaboration. - RESULTS: Search strategy identified 716 potentially eligible articles, of which 12 papers regarding 10 SRs were included in the study. Results from different SRs showed that subepithelial connective tissue grafts associated or not to coronally advanced flaps can be used to reduce recession depth and improve the width of keratinized tissue. All quality assessment tools showed that most of the SRs were of good methodological quality, but they also highlighted key points that could be improved in future reviews. Only two SRs followed in full the guidelines proposed by the Cochrane Collaboration. - CONCLUSIONS: All SRs agree that RC may be anticipated by different surgical procedures. However, differences in the methodological quality between reviews were quite evident, and thus making a clear indication that there is a need of standardization of the methods that will be applied by future SRs. As a result, a standardized checklist for reporting SRs was proposed by the authors.
Gesehen am 02.02.2023